Pengaruh Kompetensi dan Budaya Organisasi Terhadap Kepuasan Kerja Karyawan di BKPSDM Pemerintah Kota Depok - Kurnia Asri (STIKes Ibnu Sina Ajibarang, 2023)
The Depok City Human Resources Development and Personnel Agency is a government institution that handles staffing within the Depok City Government. This study aims to determine the influence of competence and organizational culture on employee job satisfaction at BKPSDM Depok City Government. The population in this study was all BKPSDM employees, with a sample of 65 respondents taken using the total sampling technique. Data was obtained using questionnaires and interviews. This research uses data quality test, validity test, reliability test, classical assumption test, multiple linear regression test and determination test. The results showed that partial competence had a significant effect on employee job satisfaction because t count (11.220) > t table (1.999) and significant values below 0.05. Partially, organizational culture has a significant effect on employee job satisfaction because t count (4.802) > t table (1.999) and the significant value is below 0.05. The results of the study based on the F test showed that the two independent variables consisting of competence and organizational culture had a significant effect on employee job satisfaction at the BKPSDM Depok City Government with F values calculated at 397.866 > 3.14 while viewed from the significance values of 0.001 < 0.05.